O nascimento do Proeja nos campi Macapá e Laranjal do Jari: uma análise histórica e crítica no Ifap (2012-2016) - MIRANDA, Ângela Maria Chaves (2024)
This study addressed the National Program for the Integration of Vocational Education with Basic Education in the Youth and Adult Education modality (Proeja) at the Federal Institute of Amapá (Ifap). The objective was to investigate the origins of Proeja within the institution. To that end, we described how the initial offering of this educational modality took place at the Macapá and Laranjal do Jari campuses. We sought to identify the individuals involved in this process and how student admission was carried out. We also examined whether teacher training occurred for those who worked in Proeja. The theoretical framework contextualized the need to offer Proeja within the Federal Network, based on the implementation decrees and a historical approach grounded in the perspectives of renowned authors, including Paulo Freire. Our research also presents a brief account of the implementation experiences of Proeja at the Federal Institute of São Paulo (IFSP) and the Federal Institute of Ceará (IFCE). From a methodological point of view, we adopted a qualitative approach, characterized by exploratory and descriptive features. The choice of a qualitative method allows for a better understanding of the phenomena studied, focusing on the experiences, perceptions, and meanings attributed by the subjects. The exploratory nature of the research investigates aspects that are still little known or understood, allowing for the identification of new perspectives and relevant issues. The descriptive aspect aims to detail the characteristics of our object of study, providing a broad and detailed view of the contexts and elements involved, without the intention of testing hypotheses or generalizing results. Data collection was carried out through document and bibliographic analysis. Based on a thorough analysis and discussion of the results, we were tasked with producing an Educational Product (EP), a requirement of the ProfEPT (Graduate Program in Vocational and Technological Education). The compilation of Narrated Chronicles, in podcast format, presents not only a historical record of Proeja but also reflections on the program’s value within the Federal Network, as well as the challenges and progress throughout its journey. It also includes a personal reflection by the researcher, describing experiences in teaching and in the family context, with excerpts from Paulo Freire’s writings, from the perspective of an emancipatory, critical education that fosters meaningful and engaged learning, prioritizing human development and the integral formation of individuals. This record may enrich other research focused on the study of Proeja.